Perbandingan Metode Canny, Prewitt, dan Sobel Pada Image Jenis-Jenis Alga Untuk Mendeteksi Tepi Citra - Ari Hidayat (JURIKOM (Jurnal Riset Komputer), 2020)
An image is a projection of a three-dimensional field into a two-dimensional surface. Scane is defined as a collection of geometric three-dimensional objects and is usually compiled based on physical by natural law, whereas, edge detection is part of image processing. Edge detection is the process of producing a boundary for an object in an image. Edge detection has several operators such as Canny, Prewitt and Sobel operators. The edge detection process in the image on the comparison of edge detection of images in algae images includes the canny, prewit and sobel methods, the first step we must do is to input the image, using photos of algae measuring 300x300 pixels. Image type of algae that will be inputted with bmp. After we input the image, the system will take the pixel value from Red, Green and Blue (RGB).